2014
DOI: 10.1097/aog.0000000000000477
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Folate and Reproductive Success Among Women Undergoing Assisted Reproduction

Abstract: Objective To evaluate prospectively the associations of folate with assisted reproductive technology outcomes within a U.S. population. Methods This analysis included women (n=232) in a prospective cohort study at the Massachusetts General Hospital Fertility Center. Diet was assessed before assisted reproductive technology treatment using a validated food frequency questionnaire. Intermediate and clinical endpoints of ART were abstracted from medical records. Generalized linear mixed models with random inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
2
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 92 publications
(88 citation statements)
references
References 24 publications
3
75
2
6
Order By: Relevance
“…Previously, we reported that pretreatment intakes of folate and vitamin B-12 were related to a higher probability of live birth among women undergoing ART in the United States (15). Whereas our results were intriguing, our assessment of folate and vitamin B-12 was limited to self-reported dietary assessment with a food-frequency questionnaire.…”
Section: Introductionmentioning
confidence: 73%
“…Previously, we reported that pretreatment intakes of folate and vitamin B-12 were related to a higher probability of live birth among women undergoing ART in the United States (15). Whereas our results were intriguing, our assessment of folate and vitamin B-12 was limited to self-reported dietary assessment with a food-frequency questionnaire.…”
Section: Introductionmentioning
confidence: 73%
“…Tests for trend were conducted across categories by using the median 25(OH)D concentrations in each category as a continuous variable in the regression models. To account for potential confounders, multivariable models included terms for age, race, BMI, infertility diagnosis, season when the sample was taken, dietary factors previously related to treatment outcomes in this population (20), and overall food choices as captured by 2 dataderived dietary patterns (21). The dietary patterns were identified via factor analysis with orthogonal transformation based on 40 predefined food groups by using the FACTOR procedure with Varimax rotation option in SAS (SAS Institute Inc.) as previously described (21).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the welldocumented association between folate supplementation and prevention of neural tube defects (NTDs) [23,24], periconceptional folic acid use is associated with epigenetic changes in insulin-like growth factor 2 in the child that may affect intrauterine programing of growth and development with consequences for health and disease throughout life [25]. Supplemental folate was also associated with higher live birth rates after assisted reproductive technology treatment [26], and reduced risks of spontaneous abortion [27], and congenital heart defects [28].…”
Section: Folatementioning
confidence: 99%